Study on the Reliability of Materials and Structures of Simple Pre-cast Modular Houses (Case Study: RUCAST Technology) - Muhammad Aprilia Devino; Muhammad Rusli; Ferri Eka Putra (Jurnal Permukiman, 2026)
RUCAST (PreCAST Concrete Main Frame) is a precast concrete housing system developed to provide more flexible and affordable landed houses. Unlike many existing precast technologies that have rigid panel sizes and limited floor-plan flexibility, RUCAST allows flexible beam-column positioning and flat wall columns, resulting in more efficient space usage and adaptable interior layouts. RUCAST is designed as a confined masonry structural system, where the walls carry structural loads while beams and columns function mainly as wall restraints. The system uses a concrete mix ratio of 1:2:3 (cement:fine aggregate:coarse aggregate) to ensure practical construction and consistent field quality. Beam and column dimensions are 100 × 100 mm², with mechanical connections using steel threads and plates, making the frame unsuitable as a moment-resisting system. The study evaluated material properties, structural components, structural behavior, and production costs. Tests included concrete compressive strength, reinforcing steel strength, mortar strength, masonry bond strength, flexural testing of structural components, and cyclic testing of wall systems. Results indicate that RUCAST can be applied in 37 of Indonesia’s 38 provincial capitals for hard, medium, and soft soil conditions, with adequate performance for areas having SDS ≤ 1.38g. RUCAST production costs are also approximately 25.28% lower than comparable precast housing technologies.